Framtidens behov av integrerad display på värmepumpar - Höglund, Anna; Nolemo, Klara (My University, 2025)
This thesis investigates the future need for an integrated display on heat pumps with a focus on user experience. The study is conducted in collaboration with NIBE and is based on their S-series that offers both an integrated display and an app for communicating with the heat pump. The aim is to evaluate whether a physical display is necessary for future heat pumps and how the interface design influences usability and long-term functionality. The research includes interviews with consumers and installers, a user survey, market analysis and a brief sustainability assessment. The results show that user needs vary depending on technical interest and experience. Apps are valued for their flexibility and remote control capabilities while the integrated display provides reliability and security during connectivity issues. Therefore, both the display and app are recommended to be available for future heat pumps. The user interface should be intuitive, offer different user modes and provide clear information regarding settings and system status. Additionally, alignment between the app and display interfaces is crucial to ensure consistency and ease of use. The conclusion is that an integrated display remains essential for ensuring user friendliness and reliability, but should be complemented with an app to meet different user needs